Performance of the Alere i RSV assay for point-of-care detection of respiratory syncytial virus in children - Schnee, Sarah Valerie; Pfeil, Johannes; Tabatabai, Julia; Schnitzler, Paul (BMC infectious diseases, 2017)
Respiratory syncytial virus (RSV) is the most important cause of severe acute respiratory tract infection in young children. Alere i RSV is a novel molecular rapid test which identifies respiratory syncytial virus in less than 13 min.